SEJARAH PERKEMBANGAN KERATON CIREBON (1452 – 1680 M.) - Hernawan, Wawan (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT This study aims at reconstructing the history of the development of the Kraton Cirebon based on museum information, libraries, archives, and the community. It employed qualitative research through four stages in historical research methods, namely: heuristics, criticism, interpretation, and historiography. Ibn Khaldun's cycle theory with a multidisciplinary approach was used to enrich the study. The study found that Kraton Cirebon that was finally divided into Kasepuhan, Kanoman, and Kacirebonan kraton formed from the war of influence from the rulers of Java at that time, namely the Sultanates of Mataram, Banten, and Cirebon. The study concludes that Kraton Cirebon was a strategic choice of Banten Sultanate leader in protectting the Cirebon Sultanate from the competitions among brothers (both descendants of Sunan Gunung Djati), even though it ended up weakening the sultanate. This research is important as a basic reference for micro-political history in the development of the History of Islamic Civilization in West Java and Indonesia. Keywords: Cirebon kraton, Colonial, History, Sultan. ABSTRAK Tujuan penelitian ini untuk melakukan rekonstruksi historis mengenai sejarah perkembangan keraton di Cirebon berdasarkan sumber-sumber yang tersimpan di museum, perpustakaan, tempat arsip, dan masyarakat. Jenis penelitian yang dipakai adalah penelitian kualitatif melalui empat tahapan dalam metode penelitian sejarah, yaitu: heuristik, kritik, interpretÂtasi, dan historiografi. Teori siklus dari Ibn Khaldun dengan pendekatan multidisipliner sengaja digunakan untuk memperkaya kajian. Hasil dan pembahasan penelitian ini adalah sejarah perkembangan keraton di Cirebon sejak didirikan hingga terpecah menjadi Keraton Kasepuhan, Kanoman, dan Kacirebonan yang terbentuk dari perebutan pengaruh dari penguasa Jawa saat itu, yaitu Kesultanan Mataram, Banten, dan Cirebon. Kesimpulan penelitian ini adalah pilihan strategi dari penguasa Kesultanan Banten dalam pengayoman kepada para pihak dari Kesultanan Cirebon yang merupakan saudara (sama-sama keturunan Sunan Gunung Djati), meskipun berujung melemahkan kesultanan itu karena saling berebut pengaruh pula di Cirebon. Penelitian ini menjadi penting sebagai rujukan dasar sejarah politik-mikro dalam perkembangan Sejarah Peradaban Islam di Jawa Barat dan Indonesia. Kata Kunci: Keraton Cirebon, Kolonial, Sejarah, Sultan.